2016 Annual Report of the University of Kansas Health System Poison Control Center - Thornton, Stephen L.; Oller, Lisa; Coons, Doyle M. (Kansas Journal of Medicine, 2019)
Introduction. This is the 2016 Annual Report of the University ofKansas Health System Poison Control Center (PCC). The PCC is oneof 55 certified poison control centers in the United States and servesthe state of Kansas 24 hours a day, 365 days a year, with certified specialistsin poison information and medical toxicologists. The PCCreceives calls from the public, law enforcement, health care professionals,and public health agencies. All calls to the PCC are recordedelectronically in the Toxicall® data management system and uploadedin near real-time to the National Poison Data System (NPDS), whichis the data repository for all poison control centers in the U.S.Methods. All encounters reported to the PCC from January 1, 2016to December 31, 2016 were analyzed. Data recorded for each exposureincludes caller location, age, weight, gender, substance exposedto, nature of exposure, route of exposure, interventions, medicaloutcome, disposition and location of care. Encounters were classifiedfurther as human exposure, animal exposure, confirmed non-exposure,or information call (no exposure reported).Results. The PCC logged 21,965 total encounters in 2016, including20,713 human exposure cases. The PCC received calls from everycounty in Kansas. The majority of human exposure cases (50.4%, n =10,174) were female. Approximately 67% (n = 13,903) of human exposuresinvolved a child (defined as 19 years or less). Most encountersoccurred at a residence (94.0%, n = 19,476) and most calls (72.3%, n= 14,964) originated from a residence. The majority of human exposures(n = 18,233) were acute cases (exposures occurring over eighthours or less). Ingestion was the most common route of exposuredocumented (86.3%, n = 17,882). The most common reported substancein pediatric encounters was cosmetics/personal care products(n = 1,362), followed by household cleaning products (n = 1,301). Foradult encounters, sedatives/hypnotics/antipsychotics (n = 1,130) andanalgesics (n = 1,103) were the most frequently involved substances.Unintentional exposures were the most common reason for exposures(81.3%, n = 16,836). Most encounters (71.1%, n = 14,732) weremanaged in a non-healthcare facility (i.e., a residence). Among humanexposures, 14,679 involved exposures to pharmaceutical agents while10,176 involved exposure to non-pharmaceuticals. Medical outcomeswere 32% (n = 6,582) no effect, 19% (n = 3,911) minor effect, 8% (n =1,623) moderate effect, and 2% (n = 348) major effects. There were 15deaths in 2016 reported to the PCC. Number of exposures, calls fromhealthcare facilities, cases with moderate or major medical outcomes,and deaths all increased in 2016 compared to 2015.Conclusions. The results of the 2016 University of Kansas HealthSystem Poison Control annual report demonstrates that the centerreceives calls from the entire state of Kansas totaling over 20,000human exposures per year. While pediatric exposures remain themost common, there is an increasing number of calls from healthcarefacilities and for cases with serious outcomes. The experience of thePCC is similar to national data. This report supports the continuedvalue of the PCC to both public and acute health care in the state ofKansas. Kans J Med 2018;11(2):24-33.